Identification of a Penicillium oxalicum fungus isolate and its pathogenicity against Panonychus citri (McGregor) - Du, Danchao; Lyu, Jia; Huang, Zhengdong; An, Baoju; Zhu, Li; Pu, Zhanxu; Liu, Shunmin; Hu, Xiurong; Lu, Lianming (Frontiers in Microbiology, 2025)
To obtain efficient biocontrol fungi against Panonychus citri, this study systematically identified the highly pathogenic strain HYC2101 through an analysis of its cultural characteristics, physiological and biochemical properties, and molecular identification. The isolate was identified as Penicillium oxalicum. In laboratory observations using stereomicroscopy and scanning electron microscopy, the infection process of P. oxalicum HYC2101 in P. citri was documented, and its pathogenicity against female adults and larvae was determined. The optimal temperature range for the mycelial growth and conidial production of P. oxalicum HYC2101 was found to be 25–35°C, with the highest sporulation on SDAY (sabouraud dextrose yeast extract agar medium). Observations of the infection process revealed that conidia easily attached to the cuticular folds and setae of the mite. After 24 h, the spores germinated and penetrated the cuticle. By 48 h, the hyphae had invaded the mite’s interior through the cuticle, mouthparts, and anus. At 96 h, the mite’s body was fully covered with hyphae and a large number of spores, ultimately leading to the death of the host. The results of the pathogenicity tests indicated that strain HYC2101 was significantly pathogenic to both female adults and larvae, with greater pathogenicity against female adults. The LC50 values after 7 days of infection were 5.92 × 10⁴ and 9.22 × 105 spores/mL for female adults and larvae, respectively. Under the highest spore concentration of 1 × 108 spores/mL, the LT50 values for female adults and larvae were 2.80 and 4.79 days, respectively. In conclusion, the highly pathogenic P. oxalicum strain HYC2101 shows significant potential for use in the green prevention and control of citrus red mites and warrants further development as a biocontrol resource.